2019
DOI: 10.1002/jcla.23128
|View full text |Cite
|
Sign up to set email alerts
|

AKIP1 expression in tumor tissue as a new biomarker for disease monitoring and prognosis in non‐small cell lung cancer: Results of a retrospective study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: A-kinase-interacting protein 1 (AKIP1) has been reported as an oncogenetic factor in multiple cancers; however, no study has reported its role in nonsmall cell lung cancer (NSCLC) yet. This study aimed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…According to a previous study, 9 the adjusted hazard ratio (related to DFS) for AKIP1 high vs low was 1.7. Based on which, a two‐sided log‐rank test with an overall sample size of 204 subjects achieved 90.1% power at a 0.050 significance level to detect a hazard ratio of 1.70.…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…According to a previous study, 9 the adjusted hazard ratio (related to DFS) for AKIP1 high vs low was 1.7. Based on which, a two‐sided log‐rank test with an overall sample size of 204 subjects achieved 90.1% power at a 0.050 significance level to detect a hazard ratio of 1.70.…”
Section: Methodsmentioning
confidence: 85%
“…Recent studies have confirmed AKIP1 as a potential prognostic marker in several solid cancers 9,17,19 . For instance, CRC patients with positive tumor AKIP1 expression obviously have poorer OS rates when compare with those with negative tumor AKIP1 expression 19 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations